Providing Certainty in Murabahah Agreements for Subsidized Home Ownership Financing: Relating the Role of Notary and PPAT - fitriyani, hilda (Jurnal Pengabdian West Science, 2025)
This community service program focuses on the role of Notaries and PPAT (Land Deed Officials) in providing legal certainty in financing subsidized home ownership through Murabahah contracts. The purpose of this community service is to increase understanding of the importance of these two professions in ensuring the legality of home financing agreements. The method used is descriptive qualitative with a participatory approach, which involves observation, semi-structured interviews, and documentation studies. The results of the service showed that collaboration between Notary and PPAT is essential in creating authentic deeds that protect the rights of all parties involved, thus facilitating access to affordable housing for low-income people. Translated with DeepL.com (free version)